Dispensing doctor practices and community pharmacies: exploring the quality of pharmaceutical services. Issue 1 (17th March 2015) - Weiss, Marjorie C.; Grey, Elisabeth; Harris, Michael; Rodham, Karen
Abstract : Aims: This research sought (a) to investigate the similarities and differences in how pharmaceutical services are provided by community pharmacies (CPs) and dispensing doctor practices (DPs) and (b) to identify the issues relevant to determining the quality of pharmaceutical services in these settings. Background: UK pharmaceutical services, including dispensing prescriptions and public health advice, can be provided from both (CP) and, in rural areas, (DP). While there is much similarity between CPs and DPs in the types of services provided, there is also the potential for variation in service quality across settings. Methods: A postal questionnaire of DPs and CPs in South West England was conducted to provide a descriptive overview of pharmaceutical services across the settings. A subsection of questionnaire respondent sites were selected to take part in case studies, which involved documentary analyses, observation and staff interviews. Findings: Survey response was 39% for CPs (52/134) and 48% (31/64) for DPs. There were three CP and four DP case study sites, with 17 staff interviews. More pharmacies than practices were open at the weekend and they had more staff trained above NVQ level 2. Both doctors and pharmacists saw themselves as medicines experts, as being accessible and having good relationships with patients. Workplace practices and organisational ethos varied both within and across settings, with good practice observed in both. Overall, CPs and DPs have much in common. Workplace culture and an evidence-based approach to checking prescriptions and error reporting need to be considered in future assessments of service quality.